The Impact of Guided Inquiry Learning on Student Performance in Electrolyte and Nonelectrolyte Materials: A Case Study at SMA Negeri 1 Batang Onang - Harahap, Shintia Putri; Nasution, Mariam; Siregar, Nur Fauziah (LAVOISIER: Chemistry Education Journal, 2024)
This study aims to see the effect of the Guided Inquiry Learning Model on Student Learning Outcomes on the Material of Electrolyte and Non-Electrolyte Solutions of Class X Students at SMA Negeri 1 Batang Onang. The learning outcomes of high school students in chemistry are still relatively low, one of which is caused by the dominance of teachers in a less innovative learning process that makes students passive. The research was conducted at SMA N 1 Batang Onang with a research sample of two classes: class X MIA-2 (control class) with 16 male students and 12 female students, and class X MIA-3 (experimental class) with 14 male students and 13 female students. This research method is an experiment with a non-randomized group pre-test post-test design. The instrument used was an essay test of 5 questions. The results showed a significant increase in student learning outcomes after the application of the guided inquiry learning model. In conclusion, the guided inquiry learning model is effective in improving student learning outcomes in chemistry learning. The results of hypothesis testing using T Test (Independent Sample t Test). This is evidenced based on the calculation of hypothesis testing with an average test taken from the pretest and posttest scores that the results of the posttest independent sample t test with a significant level value (α = 0.05) obtained a significant value (2-tailed) of 0.008. The significant value (2-tailed) obtained is smaller than 0.05, so H0 is rejected and Ha is accepted. This shows that there is an effect of guided inquiry learning model on student learning outcomes in the material of electrolyte and non-electrolyte solutions in class X SMA N 1 Batang Onang.